Enacting student partnership as though we really mean it: Some Freirean principles for a pedagogy of partnership - Peters, John; Mathias, Leoarna (International Journal for Students as Partners, 2018)
The idea of student-staff partnership working is becoming increasingly popular in higher education. However, there is a risk that, as the idea spreads, the radical nature of partnership working can be diluted and domesticated by established power structures. This article explores the theoretical and practical implications of adopting approaches to partnership working informed by the ideas of Paulo Freire. This is partnership working with a political point—consciously seeking to resist the forces of neoliberalism and any attempts to domesticate partnership to that paradigm. Instead, a pedagogy of partnership, informed by Freire, is juxtaposed with neoliberal domesticated partnership, and six principles are offered for enacting partnership as though we really mean it.